GTOC-11: Results from the University of Alabama. (January 2023) - Sikes, Jared D.; Pezent, James B.; Sandel, Carrie G.; Rubinsztejn, Ari; Sood, Rohan
Abstract: In this work, Team ASRL's solution approach for the 11th Global Trajectory Optimization Competition (GTOC-11) is described. This problem tasked the competing teams with constructing a futuristic Dyson Ring utilizing materials acquired from the asteroid belt. In total, 10 motherships would depart from Earth in the year 2121 and visit as many asteroids as possible. After visiting each asteroid, a low-thrust propulsion module would transfer the material down to the desired final Dyson stations. The final approach utilized a deterministic tree search that involved alternating between fixed time of flight Lambert searches and solutions to the full-fidelity optimal control problem. Once a single tour had been constructed, transfer trajectories were computed for each asteroid to as many of the building stations as possible. After computing a pool of thousands of these completed legs, a bin packing algorithm was used to determine the highest scoring combination of 10 solutions. This search process was implemented in Python using the soon-to-be-released trajectory optimization tool, ASSET. Ultimately, the team finished 5th with a score of 5525.38. Highlights: GTOC11 results from the Astrodynamics and Space Research Laboratory (ASRL) team. Selection of asteroid population subsets based on mean deliverable mass to stations. Deterministic beam search algorithm with full-fidelity optimal control solutions. A bin packing algorithm for minimizing variance in final Dyson station mass.